2021
DOI: 10.3390/genes12060825
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Alzheimer’s Disease Is Associated with Enlargement of Perivascular Spaces in Centrum Semiovale Region

Abstract: This study investigated whether genetic factors involved in Alzheimer’s disease (AD) are associated with enlargement of Perivascular Spaces (ePVS) in the brain. A total of 680 participants with T2-weighted MRI scans and genetic information were acquired from the ALFA study. ePVS in the basal ganglia (BG) and the centrum semiovale (CS) were assessed based on a validated visual rating scale. We used univariate and multivariate logistic regression models to investigate associations between ePVS in BG and CS with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Our study has some limitations: First, a wide variety of imaging methods and MVPVS evaluation methods have been employed to assess MVPVS. Even within studies, the interrater agreement for MVPVS detection can be moderate to substantial (Cohen’s kappa: 0:58–0.91) ( Wang et al, 2019 ; Best et al, 2020 ; Javierre-Petit et al, 2020 ; Ciampa et al, 2021 ; Song et al, 2021 ). This heterogeneity could have biased our narrative summary.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has some limitations: First, a wide variety of imaging methods and MVPVS evaluation methods have been employed to assess MVPVS. Even within studies, the interrater agreement for MVPVS detection can be moderate to substantial (Cohen’s kappa: 0:58–0.91) ( Wang et al, 2019 ; Best et al, 2020 ; Javierre-Petit et al, 2020 ; Ciampa et al, 2021 ; Song et al, 2021 ). This heterogeneity could have biased our narrative summary.…”
Section: Discussionmentioning
confidence: 99%
“…61 In addition to the clearance mechanism of brain metabolic waste, some scholars have also elaborated on the relationship between EPVSs and AD from the perspective of tau pathophysiology, neurodegeneration, and synaptic dysfunction 62 or AD gene susceptibility. 63 Some studies have indicated that βamyloidosis and EPVSs in patients with AD are not associated with PET findings. 60 The Influence of Other Markers on the Assessment of EPVSs Should Not Be Ignored…”
Section: Epvss May Distinguish Cerebral Amyloid Angiopathy From Spont...mentioning
confidence: 99%
“…Gertje et al [ 73 ] found that enlargement of these spaces was associated with small vessel disease, but their data did not support a role in the early stages of Alzheimer’s disease pathology. In contrast, Paradise et al [ 74 ] found that severe perivascular space dilation was associated with increased chance of cognitive decline and dementia and Ciampa et al [ 75 ] reported that genetic risk factors for Alzheimer’s disease are associated with enlarged perivascular spaces in the centrum semiovalae region of the brain.…”
Section: Elements Of the Blood–brain Barrier Neurovascular Unit And B...mentioning
confidence: 99%